Agronomic Performance and Selection of Tropical Soybean Progenies Derived from Charcoal Rot (Macrophomina sp.)- Resistant Parents - da Silva, Hortência Kardec [UNESP]; Miranda, Glauco Vieira; Moitinho, Alyce Carla Rodrigues [UNESP]; Cristeli, Dardânia Soares [UNESP]; da Silva Souza, Jardel [UNESP]; Silva, Alice Pereira [UNESP]; Garcia, Thayná Pereira [UNESP]; Unêda-Trevisoli, Sandra Helena [UNESP] (MDPI, 2025)
Charcoal rot, a destructive disease of soybean roots, has limited control options, and the development of resistant cultivars is the most effective, economical, and sustainable strategy. However, tropical cultivars are generally susceptible, while exotic resistant accessions are poorly adapted to tropical conditions. This study represents the initial step toward developing tropical soybean cultivars combining resistance and agronomic performance. We evaluated the agronomic performance of progenies derived from crosses between exotic lines partially resistant to Macrophomina phaseolina (PI 594302 and PI 567562A) and three commercial tropical cultivars with high yield potential (relative maturity groups (RMGs) 5.5, 6.2, and 6.9). Populations were advanced to the F6 generation and assessed for yield, plant height, first pod insertion, and agronomic value using a partial diallel design. Grain yield ranged from 18.5 to 33.2 g·plant−1 across generations. The combining ability analysis revealed predominance of additive genetic effects, highlighting PI 594302 and VMAX RR (RMG 6.2) as key parents for plant height, agronomic value, and grain yield and exhibited the greatest potential for superior progeny across generations. These results identify promising lines with high agronomic performance and adaptation, which will undergo resistance confirmation in subsequent studies, supporting the long-term goal of developing tropical soybean cultivars that combine productivity, sustainability, and tolerance to charcoal rot.